THE USE OF JIGSAW II TECHNIQUE AND STILL PICTURES COMBINATION TO IMPROVE STUDENTS’ VOCABULARY MASTERY (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2013)
This article is about the use of Jigsaw II technique and Still Pictures combination to improve students’ vocabulary mastery. In order to achieve the objectives of this research, the writer adopted an action research design. The subject of this research was class 7B of SMP N 12 Magelang, in the academic year of 2012/2013 which consisted of 32 students. There were two cycles in this research, and there were four phases in each cycle. They were planning, action, observation, and reflection. In order to collect data about students’ vocabulary mastery improvement and responses toward the use of this technique and media, the writer used observation sheet, questionnaire, interview, and test. The result of this study showed that the combination of Jigsaw II technique and Still Pictures can improve students’ vocabulary mastery. Besides, the result of the observation sheet, questionnaire and interview revealed that the students gave very positive responses toward the use of this technique and media. Based on the result of this research, the writer concluded that the use of Jigsaw II technique and Still Pictures gave a good contribution in English teaching and learning, especially in the area of vocabulary learning.